PPE38-Secretion-Dependent Proteins of M. tuberculosis Alter NF-kB Signalling and Inflammatory Responses in Macrophages - Gallant, James; Heunis, Tiaan; Beltran, Caroline; Schildermans, Karin; Bruijns, Sven; Mertens, Inge; Bitter, Wilbert; Sampson, Samantha L. (Frontiers in Immunology, 2021)
It was previously shown that secretion of PE-PGRS and PPE-MPTR proteins is abolished in clinical M. tuberculosis isolates with a deletion in the ppe38-71 operon and this deletion is associated with increased virulence. Here we investigate the role of these proteins in the innate immune response using temporal proteomics and protein turnover analysis in a macrophage infection model. A decreased pro-inflammatory response was observed in macrophages infected with PPE38-deficient M. tuberculosis CDC1551 as compared to wildtype bacteria. We could show that dampening of the pro-inflammatory response is associated with activation of a RelB/p50 pathway, while the canonical inflammatory pathway is active during infection with wild-type M. tuberculosis CDC1551. These results indicate a molecular mechanism by which M. tuberculosis the PE/PPE proteins controlled by PPE38 have an effect on modulating macrophage responses through NF-kB signalling.